Financial inclusion: How do you know that you are there? - Jared Osoro; David Muriithi (Kenya Bankers Association (KBA), 2018)
At what point do you consider yourself financially included? This question, which is this paper's objective, is considered mundane and therefore seldom asked and consequently hardly answered. The paper anchors its assessment on the distinction between access and usage of financial services and contend that the former is a necessary but not sufficient condition without the latter for one to be considered to be financially included in an impactful way. Using a multinomial logit model, the paper makes two key inferences. First, the globally acknowledged financial innovation largely riding on mobile telephony seeks to address the inefficiencies of the dominance of cash payments. While this is a necessary step, it can only be seen as an input to the utilisation of services by financial service providers such as banks, insurance companies, MFIs and Saccos. Second, financial inclusion is income sensitive, with the probability of being included through usage of banking, insurance, MFI and Sacco services increasing as income levels rise. This is confirmed by the income parameters in the model being statistically significant and the marginal effects rising in every higher income quartile. The consideration of financial inclusion only from the access dimension and not supplementing it with the usage dimension limits the analytical ability on breaking the poverty trap using finance. This by no means discounts the relationship established by other studies between longrun poverty reduction and mobile money. It nonetheless points to the possibility that such gains in poverty reduction do not necessarily lead to a reduction in informality, in which case the ability to access a cross range of financial services is limited.
Keywords: 330; Finanzielle Inklusion; Finanzdienstleistung; Elektronisches Geld; Kenia